The study of distance changes between lumbar bi-cortical pedicle screws and anterior large vessels in patients with lumbar spondylolisthesis - Li Zhao (BMC, 2021)
Abstract Objective This paper was a anatomical radiographic study of distance between lumbar bi-cortical pedicle screws (BPSs) and anterior large vessels (ALVs) in patients with lumbar spondylolisthesis, and to provide clinical basis for evaluating the safety of bi-cortical pedicle screw implantation during lumbar spondylolisthesis. Methods Complete Computed tomography (CT) data of 104 patients with grade I lumbar spondylolisthesis (L4 52 and L5 52) and 107 non-spondylolisthesis patients (control group) were collected in this study. The distances between lumbar 4,5(L4,5) and sacrum 1(S1) BPSs and ALVs (abdominal aorta, inferior vena cava, left and right common iliac artery, internal and external iliac artery) were respectively measured at different transverse screw angles (TSAs) (L4:5°,10°; L5:10°,15°; S1:0°,5°,10°) and analyzed by SPSS (v25.0). There were three types of distances from the anterior vertebral cortex (AVC) to the ALVs (DAVC-ALV): DAVC-ALV N, DAVC-ALV ≥ 0.50 cm, and DAVC-ALV < 0.50 cm; these different distances represented non-contact, distant and close ALV respectively. Results We calculated the incidences of screw tip contacting large vessels at different TSAs and provided the appropriate angle of screw implantation. In non-spondylolisthesis group, in L4, the appropriate left TSA was 5°, and the incidence of the close ALV was 4.62%. In S1, the appropriate left TSA was 0° and the incidence of the close ALV was 22.4%, while the appropriate right TSA was 10° and the incidence of the close ALV was 17.8%. In L4 spondylolisthesis group, in L4, the appropriate left TSA was 5°, and the incidence of the close ALV was 3.8%. In L5 spondylolisthesis group, in S1, the appropriate left TSA was 0° and the incidence of the close ALV was 19.2%, while the appropriate right TSA was 10° and the incidence of the close ALV was 21.2%. The use of BPS was not appropriate on the right side of L4 or on the either side of L5 both in spondylolisthesis and control group. In patients with lumbar 4 spondylolisthesis, the incidences of screw tip contacting large vessels were less than the control group in both L4 and 5. In patients with lumbar 5 spondylolisthesis, the incidences of screw tip contacting large vessels were less than the control group in L5, while there were no significant difference in S1. Conclusion It is very important that considering the anatomical relationship between the AVC and the ALVs while planning BPSs. The use of BPS does not apply to every lumbar vertebra. In patients with lumbar spondylolisthesis and non-spondylolisthesis patients, the incidences of screw tip contacting large vessels are different.